Capsule-strip- An Unusual Cause of Acute Gastric Outlet Obstruction: A Case-Report - Rowshon, AHM; Uddin, AKM Rafique (Journal of Shaheed Suhrawardy Medical College, 2013)
A male patient presented with seven days history of severe epigastric colicky pain and vomiting. The patient was anxious and dehydrated. Blood tests and ultrasound reports were unremarkable. . Upper Gastrointestinal (GI) Endoscopy revealed a strip of capsule impacted at pyloric ring which was removed endoscopically and the patient became symptom free. DOI: http://dx.doi.org/10.3329/jssmc.v5i1.16252 J Shaheed Suhrawardy Med Coll, 2013;5(1):67-68